Design of smart garments for sports and rehabilitation - Paiva, André Luís Brasil (2018)
Physical exercise has proved benefits for general health [1] and can reduce the number of sports injuries to one third [2]. However, an athlete that has been injured during sports practice may omit this out of fear of discrimination, and worsen the injury in the weight room, during strength training [5]. Monitoring physiological status of an athlete or rehabilitation patients during training may thus help the person to get an earlier intervention, preventing injuries from getting worse. With this in mind, we propose a set of compression garments – shirt and leggings – with textile sensors to continually monitor heart and muscle activity, breathing rate and temperature. This paper reports the design of the garments and production of the shirt, which comprised a 3-lead ECG system, sEMG (Surface Electromiography) electrodes and a breathing sensor. The ECG (Electrocardiography) system was tested and presented some good results, in particular for very even movements, but the system still needs to be improved, in order to get a better signal, when it comes to movements with a considerable amplitude.